Pengaruh Work Life Balance dan Kepuasan Kerja terhadap Loyalitas Karyawan Gen-Z di Kabupaten Toraja Utara - Chrismesi Pagiu; Dian Intan Tangkeallo; Rahel Semuel Saratu (Journal of Management and Creative Business, 2026)
This study aims to analyze the effect of Work-Life Balance and Job Satisfaction on the loyalty of Generation Z employees in North Toraja Regency. This research employed a quantitative approach using a causal associative research design. The sampling technique used was simple random sampling, with a total of 100 respondents selected from a large and heterogeneous population.The results of the t-test showed that Work-Life Balance had no significant effect on employee loyalty, as indicated by a t-value of 1.186, which was lower than the t-table value of 1.661, with a significance value of 0.239 > 0.05. In contrast, Job Satisfaction had a positive and significant effect on employee loyalty, with a t-value of 2.692, which exceeded the t-table value of 1.661, and a significance value of 0.008 < 0.05. Furthermore, the F-test revealed that Work-Life Balance and Job Satisfaction simultaneously had a positive and significant effect on employee loyalty, as indicated by an F-value of 9.941, which was higher than the F-table value of 3.09, with a significance value of 0.001 < 0.05.The findings indicate that Work-Life Balance does not significantly affect the loyalty of Generation Z employees in North Toraja Regency, whereas Job Satisfaction has a positive and significant effect on employee loyalty. Furthermore, Work-Life Balance and Job Satisfaction simultaneously have a positive and significant effect on the loyalty of Generation Z employees in North Toraja Regency